-9 - 13 - (-24) + 11=
323-6[3-7.(-9)ư
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, -9-13-(-24)+11
=-22-(-24)+11
=2+11
=13
b, 323-6[3-7(-9)]
=323-6[3-(-63)]
=323-6.66
=323-396
=-73
c, (-3)^5:(-3)^3-9
=32-9
=9-9
=0
d,(-8)x16-13x8
=8x(-16)-13x8
=8x(-16-13)
=8x(-29)
=-232
1) a) -8 + 19 = 11
b) (-17) : (-3) = \(\frac{17}{3}\)
c) 4 - (-13) = 17
2) a) -9 - 13 - (-24) + 11 = 13
b) 323 - 6\([3-7.\left(-9\right)]\)= -73
c) (-3)5 : (-3)3 - 9 =0
d) (-8).16 - 13.8 = -232
3) a) -15 : x = 3
x = 3.(-15) = -45
b) -3x + 8 = -7
-3x = -15
x = 5
c) (x - 6).(7 - x) =0
=> x - 6 = 0 hoặc 7 - x = 0
x = 6 x = 7
~ Học tốt ~
Bài 1:
a) -8+19=11
b) (-27):(-3)=9
c) 4-(-13)=17
Bài 2:
a) -19-13-(-24)+11=13
b) 323-6[3-7.(-9)]=-73
c) (-3)5:(-3)3-9=0
d) (-8).16-13.8=-232
Bài 3:
a) -15:x=3
x=3.(-15)
x=-45
b)-3x+8=-7
-3x=(-7)-8
-3x=-15
x=(-15):(-3)=5
c) (x-6).(7-x)=0
=>x-6=0 hoặc 7-x=0
x=6 x=7
x=6
\(-9-13-\left(-24\right)+11\)
\(=\left(-9-13\right)+\left(24+11\right)\)
\(=-22+35\)
\(=13\)
\(a,\dfrac{-1}{7}+\dfrac{8}{13}+\dfrac{-6}{7}-1\dfrac{23}{24}-\dfrac{-5}{13}\\ =\dfrac{-1}{7}+\dfrac{8}{13}+\dfrac{-6}{7}-\dfrac{47}{24}+\dfrac{5}{13}\\ =\left(\dfrac{-1}{7}+\dfrac{-6}{7}\right)+\left(\dfrac{8}{13}+\dfrac{5}{13}\right)-\dfrac{47}{24}\\ =-1+1-\dfrac{47}{24}\\ =0-\dfrac{47}{24}\\ =\dfrac{-47}{24}\)
\(b,\left(7\dfrac{4}{9}+4\dfrac{7}{11}\right)-3\dfrac{4}{9}\\ =7\dfrac{4}{9}+4\dfrac{7}{11}-3\dfrac{4}{9}\\ =\left(7\dfrac{4}{9}-3\dfrac{4}{9}\right)+4\dfrac{7}{11}\\ =4+4\dfrac{7}{11}\\ =\dfrac{44}{11}+\dfrac{51}{11}\\ =\dfrac{95}{11}\)
`@` `\text {Ans}`
`\downarrow`
`a.`
`A=(1/2-7/13-1/3)+(-6/13+1/2+1 1/3)`
`= 1/2 - 7/13 - 1/3 - 6/13 + 1/2 + 1 1/3`
`= (1/2 + 1/2) + (-7/13 - 6/13) + (-1/3 + 1 1/3) `
`= 1 - 1 + 1`
`= 1`
`b.`
`B=0,75+2/5+(1/9-1 1/2+5/4)`
`= 3/4 + 2/5 + 1/9 - 3/2 + 5/4`
`= (3/4+5/4)+ 1/9 + 2/5 - 3/2`
`= 2 + 1/9 - 11/10`
`= 19/9 - 11/10`
`= 91/90`
`c.`
`(-5/9).3/11+(-13/18).3/11`
`= 3/11*[(-5/9) + (-13/18)]`
`= 3/11*(-23/18)`
`= -23/66`
`d.`
`(-2/3).3/11+(-16/9).3/11`
`= 3/11* [(-2/3) + (-16/9)]`
`= 3/11*(-22/9)`
`= -2/3`
`e.`
`(-1/4).(-2/13)-7/24.(-2/13)`
`= (-2/13)*(-1/4-7/24)`
`= (-2/13)*(-13/24)`
`= 1/12`
`f.`
`(-1/27).3/7+(5/9).(-3/7)`
`= 3/7*(-1/27 - 5/9)`
`= 3/7*(-16/27)`
`= -16/63`
`g.`
`(-1/5+3/7):2/11+(-4/5+4/7):2/11`
`=[(-1/5+3/7)+(-4/5+4/7)] \div 2/11`
`= (-1/5+3/7 - 4/5 + 4/7) \div 2/11`
`= [(-1/5-4/5)+(3/7+4/7)] \div 2/11`
`= (-1+1) \div 2/11`
`= 0 \div 2/11 = 0`
\(\dfrac{14}{7}>\dfrac{9}{7}\)
\(\dfrac{6}{13}< 1\)
\(\dfrac{7}{9}=\dfrac{14}{18}\)
\(\dfrac{4}{9}=\dfrac{20}{45}< \dfrac{26}{45}\)
\(\dfrac{11}{24}>\dfrac{9}{24}=\dfrac{3}{8}\)
\(\dfrac{42}{91}=\dfrac{42:7}{91:7}=\dfrac{6}{13}< \dfrac{7}{13}\)
\(\dfrac{34}{64}< \dfrac{52}{64}=\dfrac{13}{16}\)
\(\dfrac{17}{30}>\dfrac{16}{30}=\dfrac{8}{15}\)
2/3-6/12+1/4 = 5/12
4/12-18/24+5/2 = 25/12
-5/7*11/9+5/7*4/9 = -5/9
-3/8*13/11-3/8*3/11 = -6/11
-9 - 13 - (-24) + 11
= 24 - 22 + 11
= 2 + 11
= 13
323 - 6[3 - 7.(-9)
= 323 - 6.66
= 323 - 396
= -73
k nha
- 9 - 13 - ( - 24 ) + 11 323 - 6 . [ 3 - 7 . ( -9 ) ]
= - 22 - ( -24) +11 = 323 - 6 . [ -4 . ( - 9 ) ]
= 2 + 11 = 323 - 6 . 36
= 13 = 107